2022
DOI: 10.1017/s002221512100428x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review: impact of in-office biopsy on safety and waiting times in head and neck cancer

Abstract: Objective This study aimed to assess the current literature on the safety and impact of in-office biopsy on cancer waiting times as well as review evidence regarding cost-efficacy and patient satisfaction. Method A search of Cinahl, Cochrane Library, Embase, Medline, Prospero, PubMed and Web of Science was conducted for papers relevant to this study. Included articles were quality assessed and critically appraised. Results Of 19 741 identified studies, 22 articles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, most research indicates that LA biopsies are safe, and there are very few major complications reported in the literature. 8 Furthermore, the most common complications, for example bleeding, are minor and often self-limiting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most research indicates that LA biopsies are safe, and there are very few major complications reported in the literature. 8 Furthermore, the most common complications, for example bleeding, are minor and often self-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature found less than 1 per cent of procedures were abandoned because of poor tolerability. 8
Delays in the head and neck cancer pathway result in patients not meeting the 62-day target of referral for treatment In this study, 43 per cent ( n = 25) of respondents were not using local anaesthetic (LA) biopsy with channelled endoscope, but were interested in using it Advantages of LA biopsy include avoiding general anaesthetic and difficult intubation, and faster cancer pathway times Disadvantages of LA biopsy include clinic running late, complications and missing a synchronous primary cancer The main barrier to using LA biopsy is lack of access to channelled flexible endoscopy
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review by Lim et al supports the practice of biopsying head and neck tumours. 10 The findings revealed in-office biopsies to be safe and well tolerated. Furthermore, they helped certain patients avoid a general anaesthetic, significantly reduced time-to-diagnosis and time-to-treatment initiation, had high rates of sensitivity and specificity, and are likely to be cost-saving compared with operating theatre biopsies.…”
mentioning
confidence: 90%